Synthesis, structure and DNA interaction studies of bisphosphoramides: theoretical and experimental insights - Goud, E. Veerashekhar; Sivaramakrishna, Akella; Vijayakrishna, Kari; Rao, C. V. S. Brahmmananda; Khedkar, Vijay M.; Jha, Prakash C. (Inorganica Chimica Acta, 2017)
New bisphosphoramides (having phenyl (EDAPOPh(2)) and ethoxy (EDADEP) substituents attached to phosphoryl groups bridged with ethylenediamine spacer) are synthesized and structurally characterized by spectroscopic techniques as well as elemental analysis. The molecular structure of EDAPOPh(2) was determined by single crystal X-ray diffraction technique. The interaction of these bisphosphoramides with calf thymus DNA (ct-DNA) is investigated using UV-Visible absorption and fluorescence spectral data as well as the DFT calculations. These studies reveal that EDAPOPh(2) and EDADEP interact with DNA in a partial intercalation mode. The intrinsic binding constants K-b of two different bisphosphoramides with ct-DNA were determined by fluorescence spectroscopy as 2.08 x 10(4) and 3.86 x 10(4) M-1 respectively. The results indicated that the two compounds bind to ct-DNA with different binding affinities, i.e. EDAPOPh(2) > EDADEP. The binding mechanism of these bisphosphoramides to ct-DNA is also discussed. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Bisphosphoramides; crystal structure; DNA interaction; Molecular docking